Financial Resources in Third Sector Organizations. A Comparative Study of Pan Africa and Hope Restoration Group - Ng'ang'a, Samuel James (Daystar University, 2006)
A reliable internal control structure is a fundamental success factor in financial management and eventual achievement of organizational goals because it ensures effectiveness and efficiency of financial operations. The purpose of this study was to assess the reliability of internal control structures in safeguarding financial resources in third sector organizations, taking a comparative study of Pan Africa and Hope Restoration Group (HRG). The researcher used descriptive research and targeted a population of 54 and 104 people for Pan Africa and HRG respectively. Data was collected using a questionnaire, interviews and observations from a sample size of 94% and 65% of the population of Pan Africa and HRG, respectively. Stratified sampling and purposive sampling techniques were used due to heterogeneity of the target population. Data was analyzed using SPSS software. Content analysis was also done and data is presented using tables and cross tabulations. Results revealed that although Pan Africa had relatively stronger internal control structure compared to HRG, internal controls in both organizations were reliable to an extent of 77% and 72% for Pan Africa and HRG respectively. This was an indication that internal control structures in Pan Africa and HRG had limitations in safeguarding financial resources. Review of internal control structures in both entities is therefore necessary to enhance reliability.
Master's Thesis
Keywords: internal control structures; Pan Africa and Hope Restoration Group (HRG).